Green low-carbon high-efficiency energy-saving composite material for reinforcing existing masonry house
By using components such as fly ash, slag, Portland cement, fibers and high-strength vitrified microspheres in the reinforcement materials, the deficiencies in energy saving, environmental protection and strength performance of the existing reinforcement materials are solved, and high performance, Low-carbon, energy-saving green low-carbon energy-saving composite materials.
Patent Information
- Application Number
- CN202411467372.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-21
AI Technical Summary
The existing reinforcement materials have insufficient energy saving, environmental protection and strength performance, which is difficult to meet the requirements of modern green buildings for energy saving and environmental protection.
Composite materials using components such as fly ash, slag, Portland cement, fibers and high-strength vitrified microspheres. Through precise component ratio design, the mechanical properties, crack resistance, thermal insulation effect and durability of the material are improved. sex.
It significantly improves the mechanical properties and crack resistance of the material, greatly improves the thermal insulation effect and durability, meets stringent green building standards, and has excellent corrosion resistance, freeze-thaw resistance, and acid and alkali resistance.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of green, low-carbon, high-efficiency and energy-saving reinforcement materials, and specifically relates to a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses. Background Art
[0002] In recent years, with the rapid development of the construction industry, the demand for reinforcement materials has increased dramatically. However, traditional reinforcement materials have problems of high energy consumption and high carbon emissions during production and application, which seriously affects the sustainable development of the environment. At the same time, the safety, durability and energy-saving performance of buildings have also become the focus of social attention. How to develop new green, low-carbon and energy-saving building materials while ensuring the high performance of building materials has become an important research topic in the construction industry. In recent years, studies have shown that by applying industrial solid waste to the research and development of building materials, it can not only effectively reduce the stockpile of solid waste and reduce environmental pollution, but also achieve high performance and sustainable development of building materials through reasonable material ratios.
[0003] In practical applications, although traditional reinforcement materials have certain strength and durability, their thermal conductivity is high and their thermal insulation performance is poor, making it difficult to meet the energy-saving and environmental protection requirements of modern green buildings. As a new type of lightweight thermal insulation material, high-strength vitrified microspheres have broad application prospects in the construction field due to their advantages such as low thermal conductivity, high temperature resistance, and high compressive strength. Therefore, a reasonable ratio of high-strength vitrified microspheres with fly ash, slag, cement and other materials can effectively improve the thermal insulation performance of traditional reinforcement materials, while improving the mechanical properties of the materials and reducing the weight of the materials. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in view of the deficiencies of the above-mentioned prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses, characterized in that the composite material includes the following components by mass fraction: 20 to 26 parts of fly ash, 20 to 25 parts of slag, 10 to 16 parts of silicate cement, 8 to 10 parts of high-strength vitrified microspheres, 0.5 to 1.5 parts of fiber, 0.2 to 0.5 parts of water reducer, and 15 to 30 parts of water.
[0006] The present invention aims to solve the deficiencies of existing reinforcement materials in energy saving, environmental protection and strength performance, and proposes a green, low-carbon, energy-saving, high-performance reinforcement material based on fly ash, slag, silicate cement, fiber and high-strength vitrified microspheres. The material is designed through precise component ratio, especially the introduction of high-strength vitrified microspheres and fibers, which not only significantly improves the mechanical properties and crack resistance of the material, but also greatly improves its thermal insulation effect and durability. Fly ash and slag are used as main raw materials. While maintaining the high strength of the material, efficient recycling of industrial solid waste is achieved, and carbon emissions in the production process are reduced. The 28-day compressive strength of the material can reach more than 10MPa, and the thermal conductivity is lower than 0.35W / (m·K), which can meet the strict green building standards. The construction process is simple, the material has high early strength, and the construction period is shortened. The material has excellent corrosion resistance, freeze-thaw resistance and acid and alkali resistance, and is particularly suitable for construction projects in complex environments such as severe cold, humidity, and underground, and has broad application prospects.
[0007] The green, low-carbon and energy-saving composite material described in the present invention adopts fly ash, slag, silicate cement and high-strength vitrified microspheres as basic raw materials, and adds fibers and water reducers, aiming to significantly improve the strength, durability and environmental performance of building materials through the synergistic effect of multiple components. The recycling of fly ash and slag as industrial solid waste resources not only reduces the cost of raw materials, but also effectively reduces carbon emissions, with significant environmental benefits. The lightweight characteristics of vitrified microspheres enable the material to have high strength while having good thermal insulation effects, effectively improving the energy efficiency performance of the building. The addition of fibers improves the crack resistance and bending resistance of the material, and the use of water reducers reduces the use of water in the preparation process of the material, improves the density and mechanical properties of the material, thereby meeting the multiple needs of modern buildings for environmental protection, energy saving and high performance.
[0008] Fly ash and slag are the main industrial solid waste components in the present invention, and the addition amount reaches more than 40% of the total amount, which can not only reduce the dependence on natural raw materials, but also enhance the compressive strength and durability of the material through their unique physical and chemical properties. The active components in fly ash and slag react with calcium ions generated by silicates in cement during the hydration process of cement to generate stable hydrated calcium silicate (C-S-H) gel. This gel is one of the key components that determine the strength and durability of the material and is beneficial to enhancing the strength of the material. Although their activity is lower than that of cement, they can replace part of the cement under a certain ratio through synergistic effect with cement, and even exceed the cement in quantity. At the same time, the overall strength of the material is maintained. In addition, fly ash and slag can fill the tiny pores in the cement slurry, increase the density of the material, thereby reducing the porosity and enhancing corrosion resistance. Compared with ordinary reinforcement materials, this design greatly extends the service life of building materials. In addition, cement has a higher early strength, while fly ash and slag react relatively slowly, which is mainly reflected in the increase in later strength. Therefore, when the proportion of fly ash and slag in the formula exceeds that of cement, the material may exhibit a slower early strength, but will achieve continuous growth in strength in the later stage to meet the use requirements, thereby realizing the use of lower-cost fly ash and slag instead of cement, and achieving green, low-carbon and high-efficiency energy saving.
[0009] The high-strength vitrified microspheres introduced in the present invention serve as lightweight fillers and have excellent thermal insulation properties. The vitrified microspheres are a material with a hollow structure. The tiny hollow spheres can effectively block heat conduction and significantly reduce the thermal conductivity of the material, thereby improving the thermal insulation performance of the building material. In severe cold or high temperature environments, building structures using the material can maintain a relatively stable indoor temperature and reduce the impact of the external environment on internal heat. At the same time, the high-strength vitrified microspheres also have the advantages of high compressive strength and stable chemical properties, so that the material has high compressive resistance and durability while maintaining its lightness. In addition, the light and high-strength properties of the high-strength vitrified microspheres are combined with the anti-cracking reinforcement effect of the fibers to provide the material with additional structural strength and toughness. The reinforcement effect partially makes up for the disadvantage of the low activity of fly ash and slag, so that the overall performance of the material can be maintained or even improved under the premise of reducing cement.
[0010] The fiber material in the present invention significantly improves the toughness and bending resistance of the reinforced material by improving its crack resistance. Fiber, as a reinforcing material, can form a uniformly distributed network structure in the material, effectively resisting the generation and expansion of cracks, and is particularly suitable for building structures that require high crack resistance. The addition of fiber not only improves the mechanical properties of the material, but also enhances its earthquake resistance and impact resistance, thereby extending the service life of the building. In addition, the fiber material has strong durability, good corrosion resistance, and can adapt to adverse climate and environmental conditions, further improving the comprehensive performance of the material.
[0011] The application of water reducer plays a key role in the material formula of the present invention. By using water reducer, the amount of water required for the material in the preparation process can be effectively reduced without affecting the workability of the material. The water reducer can significantly improve the fluidity and workability of the material, reduce the water-cement ratio in the mixture, so that even if more fly ash and slag are used, the fluidity and strength of the material can be guaranteed, thereby reducing the amount of cement while still maintaining good mixing and molding performance, thereby improving the density and compressive strength of the material. At the same time, reducing the presence of excess water can also effectively reduce the porosity of the material, reduce the risk of shrinkage cracking, and improve the overall durability and impermeability of the material. Therefore, the introduction of water reducer and the control of its dosage make the building material not only have high strength, but also have excellent durability and energy-saving and environmental protection characteristics.
[0012] The green, low-carbon and energy-saving composite material of the present invention not only has high strength and excellent thermal properties, but also has superior durability and environmental adaptability. Since glass beads, fibers and water reducers are added to the formula, the material can still maintain its excellent performance under harsh environmental conditions such as humidity, high temperature and severe cold. The corrosion resistance of the material is particularly outstanding, and it can effectively resist corrosion in acidic and alkaline environments. It is suitable for use in highly corrosive building environments such as underground, oceans or chemical plants. In addition, the material performs well in long-term freeze-thaw cycle tests, and its freeze-thaw resistance is much higher than that of traditional reinforcement materials, ensuring its wide application in cold areas.
[0013] The green, low-carbon, energy-saving composite material in the present invention also performs well in energy conservation and environmental protection. By selecting industrial solid wastes such as fly ash and slag as the main raw materials, the consumption of natural resources is reduced and carbon emissions are greatly reduced. These industrial solid wastes are reasonably proportioned and processed, which not only gives the material excellent mechanical properties, but also improves its durability and crack resistance. In addition, the thermal insulation effect of the glass microspheres can effectively reduce the energy consumption of buildings, reduce the use of air conditioners in summer, and reduce the demand for heating in winter, thereby significantly reducing the energy expenditure of buildings. Since the material has a low thermal conductivity, its thermal insulation effect enables the building to maintain a comfortable indoor temperature, which helps to promote the development of energy-saving buildings. At the same time, the production and application process of the material has low energy consumption, which further meets the requirements of green buildings and energy conservation and environmental protection. Therefore, the green, low-carbon, energy-saving composite material of the present invention has excellent performance in construction projects.
[0014] The green, low-carbon, energy-saving composite material construction process of the present invention is simple and efficient, suitable for large-scale industrial production and application. During the preparation and construction of the material, no additional complex equipment or process is required, which can significantly shorten the construction period and reduce labor costs. In addition, the material can harden quickly after construction and reach initial strength in a short time, reducing the risk of construction delays. Its good fluidity and workability make the material easy to spread during construction and can achieve uniform coating. It is particularly suitable for the repair and reinforcement of complex building structures. Overall, the material has broad prospects for promotion and application.
[0015] The green, low-carbon and energy-saving composite material of the present invention has significant superiority in performance. Its 28-day compressive strength can reach more than 10MPa, and its thermal conductivity is as low as 0.35W / (m·K), which has good thermal insulation effect. The crack resistance and bending resistance of the material are also greatly improved, and the stability of the structure can be maintained under different stress environments. In addition, the material has outstanding performance in impact resistance and seismic resistance, and is particularly suitable for the reinforcement and repair of structures such as high-rise buildings, bridges and tunnels. The superior performance of the material provides higher safety and long-term use value for construction projects.
[0016] The green, low-carbon and energy-saving composite material of the present invention has excellent durability and waterproof performance. Due to the addition of water reducing agent and high-strength vitrified microspheres, the density of the material is greatly improved, the porosity is reduced, and the permeability of the material to water is greatly reduced. Even if it is exposed to a humid or water-immersed environment for a long time, the material can still maintain its mechanical properties and structural stability. In addition, the material has excellent anti-freeze and thaw properties and can still maintain its integrity and compressive strength in repeated freeze-thaw cycles. It is particularly suitable for construction projects in cold areas.
[0017] The present invention aims to utilize a large amount of industrial solid waste such as fly ash and slag, and reduce the amount of cement by reasonably optimizing the proportion. At the same time, it combines multiple components such as high-strength vitrified microspheres, fibers and water reducing agents to develop a green, low-carbon, energy-saving, high-performance reinforcement material with low thermal conductivity, high compressive strength and good construction performance. Compared with traditional reinforcement materials, the material not only has excellent mechanical properties and durability, but also can significantly improve the thermal insulation performance of buildings, reduce the cost of building reinforcement and reconstruction, especially in the field of urban renewal, not only can it realize the reinforcement of masonry houses, but also can be used as insulation materials, greatly reducing the cost of house reinforcement and reconstruction; since the material is mainly composed of industrial solid waste, while meeting the energy conservation and environmental protection requirements of modern green buildings, it provides a new solution for the development of green buildings. In future applications, the material will be able to be widely used in the field of reinforcement and energy-saving reconstruction of buildings, effectively improve the overall performance of buildings, and reduce building energy consumption while ensuring building safety, so as to contribute to promoting the green transformation and sustainable development of the construction industry.
[0018] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the composite material includes the following components by mass fraction: 21-25 parts of fly ash, 21-23 parts of slag, 12-15 parts of Portland cement, 8-10 parts of high-strength vitrified microspheres, 0.8-1.5 parts of fiber, 0.4-0.5 parts of water reducer, and 25-28 parts of water.
[0019] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the composite material includes the following components by mass fraction: 25 parts of fly ash, 23 parts of slag, 15 parts of silicate cement, 8 parts of high-strength vitrified microspheres, 1.5 parts of fiber, 0.5 parts of water reducer, and 27 parts of water.
[0020] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the fibers are polypropylene fibers with a length of 6 mm to 12 mm.
[0021] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the water reducer is a polycarboxylic acid-based high-efficiency water reducer.
[0022] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the particle size of the high-strength vitrified microspheres is 1mm to 2mm, the compressive strength is greater than 2MPa, and the bulk density is 100kg / m 3 ~200kg / m 3 , water absorption rate is less than 5%.
[0023] The above-mentioned green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses is characterized in that the building material prepared by the composite material has a compressive strength of not less than 10 MPa and a thermal conductivity coefficient of less than 0.35 W / m·K during a curing period of 28 days.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The present invention proposes a green, low-carbon, energy-saving, high-performance reinforcement material based on fly ash, slag, silicate cement, fiber and high-strength vitrified microspheres. The material is designed with precise component ratios, especially the introduction of high-strength vitrified microspheres and fibers, which not only significantly improves the mechanical properties and crack resistance of the material, but also greatly improves its thermal insulation effect and durability. Fly ash and slag are used as the main raw materials, and the addition amount reaches more than 40% of the total. While maintaining the high strength of the material, it realizes the efficient recycling of industrial solid waste and reduces carbon emissions in the production process.
[0026] 2. The 28-day compressive strength of the composite material of the present invention can reach more than 10MPa, and the thermal conductivity is lower than 0.35W / (m·K), which can meet the stringent green building standards. The construction process is simple, the early strength of the material is high, and the construction period is shortened. The material has excellent corrosion resistance, freeze-thaw resistance, and acid and alkali resistance. It is particularly suitable for construction projects in complex environments such as severe cold, humidity, and underground, and has broad application prospects.
[0027] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0028] Example 1
[0029] A green, low-carbon, high-efficiency, energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 25 parts of fly ash, 23 parts of slag, 15 parts of silicate cement, 8 parts of high-strength vitrified microspheres, 1.5 parts of fiber, 0.5 parts of water reducer, and 27 parts of water.
[0030] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0031] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 60 minutes, a final setting time of 8 hours, a 28-day compressive strength of 15 MPa, a 28-day tensile bond strength of 2.5 MPa, and a 28-day tensile bond strength of 2.3 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 2.2 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.05%, no cracks are generated after solidification, and the thermal conductivity is 0.26W / (m·K).
[0032] The green, low-carbon and energy-saving composite material of this embodiment is used in the reinforcement and renovation of existing masonry houses, which significantly improves the structural strength and thermal insulation performance of existing masonry houses, effectively reduces the dead weight of existing masonry houses, improves construction efficiency, has excellent durability and performance, and is suitable for a variety of climatic conditions.
[0033] Example 2
[0034] A green, low-carbon, high-efficiency, energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 23 parts of fly ash, 21 parts of slag, 12 parts of silicate cement, 8 parts of high-strength vitrified microspheres, 1.2 parts of fiber, 0.4 parts of water reducer, and 28 parts of water.
[0035] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0036] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 55 minutes, a final setting time of 7.5 hours, a 28-day compressive strength of 14 MPa, a 28-day tensile bond strength of 2.3 MPa, and a 28-day tensile bond strength of 2.1 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 2.0 MPa. After 25 freeze-thaw cycles, no cracking or peeling occurs, the shrinkage rate is 0.06%, no cracks are generated after solidification, and the thermal conductivity is 0.28W / (m·K).
[0037] The green, low-carbon and energy-saving composite material of this embodiment is used in the reinforcement and renovation of existing masonry houses, which can effectively improve the strength and thermal insulation performance of existing masonry houses, reduce the amount of materials used, has good economy and environmental adaptability, and is suitable for existing medium and high-rise masonry houses and their renovation projects.
[0038] Example 3
[0039] A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 26 parts of fly ash, 20 parts of slag, 12 parts of silicate cement, 8 parts of high-strength vitrified microspheres, 1.2 parts of fiber, 0.4 parts of water reducer, and 25 parts of water.
[0040] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0041] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 58 minutes, a final setting time of 8 hours, a 28-day compressive strength of 13 MPa, a 28-day tensile bond strength of 2.4 MPa, and a 28-day tensile bond strength of 2.2 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 2.1 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.04%, no cracks are generated after solidification, and the thermal conductivity is 0.27W / (m·K).
[0042] The green, low-carbon, energy-saving composite material of this embodiment is used for the reinforcement and insulation of various existing masonry houses, which can significantly improve the comprehensive performance of existing masonry houses, including compressive strength and thermal insulation performance. It is suitable for construction projects in extreme climate environments and has high economic benefits and environmental friendliness.
[0043] Example 4
[0044] A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 20 parts of fly ash, 20 parts of slag, 12 parts of silicate cement, 10 parts of high-strength vitrified microspheres, 0.8 parts of fiber, 0.3 parts of water reducer, and 23 parts of water.
[0045] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0046] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 53 minutes, a final setting time of 7.7 hours, a 28-day compressive strength of 12 MPa, a 28-day tensile bond strength of 2.2 MPa, and a 28-day tensile bond strength of 2.0 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 1.9 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.07%, no cracks are generated after solidification, and the thermal conductivity is 0.30 W / (m·K).
[0047] Using the green, low-carbon, energy-saving composite material of this embodiment for the construction and reinforcement of existing masonry houses can effectively improve the structural strength and thermal insulation performance of existing masonry houses. It is suitable for construction projects in high humidity and extreme temperature environments, and exhibits excellent durability and economy.
[0048] Example 5
[0049] A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 23 parts of fly ash, 22 parts of slag, 16 parts of silicate cement, 9 parts of high-strength vitrified microspheres, 1.0 part of fiber, 0.3 part of water reducer, and 28 parts of water.
[0050] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0051] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 57 minutes, a final setting time of 8 hours, a 28-day compressive strength of 12 MPa, a 28-day tensile bond strength of 2.6 MPa, and a 28-day tensile bond strength of 2.4 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 2.3 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.05%, no cracks are generated after solidification, and the thermal conductivity is 0.32 W / (m·K).
[0052] Using the green, low-carbon, energy-saving composite material of this embodiment for the insulation layer and structural reinforcement of existing masonry houses can significantly improve the strength and thermal insulation performance of existing masonry houses, reduce the maintenance cost of existing masonry houses, and is suitable for construction projects under harsh climatic conditions, with excellent economic benefits and environmental adaptability.
[0053] Example 6
[0054] A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 20 parts of fly ash, 20 parts of slag, 10 parts of silicate cement, 8 parts of high-strength vitrified microspheres, 0.5 parts of fiber, 0.2 parts of water reducer, and 15 parts of water.
[0055] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0056] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 58 minutes, a final setting time of 7.6 hours, a 28-day compressive strength of 11 MPa, a 28-day tensile bond strength of 2.2 MPa, and a 28-day tensile bond strength of 2.1 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 2.0 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.06%, no cracks are generated after solidification, and the thermal conductivity is 0.33W / (m·K).
[0057] Using the green, low-carbon, energy-saving composite material of this embodiment for the construction and reinforcement of existing masonry houses can effectively improve the structural strength and thermal insulation performance of existing masonry houses. It is suitable for construction projects in high humidity and extreme temperature environments, and exhibits excellent durability and economy.
[0058] Example 7
[0059] A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses in this embodiment includes the following components in parts by mass: 25 parts of fly ash, 25 parts of slag, 15 parts of silicate cement, 10 parts of high-strength vitrified microspheres, 1.5 parts of fiber, 0.5 parts of water reducer, and 30 parts of water.
[0060] The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses of this embodiment is prepared by the following process: fly ash and slag are dried to ensure their activity and fineness, and then mixed with 32.5 grade general-purpose silicate cement with a particle size of 1mm to 2mm, a compressive strength of more than 2MPa, and a bulk density of 100kg / m 3 ~200kg / m 3 High-strength vitrified microspheres with a water absorption rate of less than 5%, polypropylene fibers with a length of 6mm to 12mm and polycarboxylic acid-based high-efficiency water-reducing agent are mixed and then water is added to obtain a green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses.
[0061] After testing, the green, low-carbon and energy-saving composite material of this embodiment has an initial setting time of 53 minutes, a final setting time of 7.7 hours, a 28-day compressive strength of 12 MPa, a 28-day tensile bond strength of 2.2 MPa, and a 28-day tensile bond strength of 2.0 MPa under water-saturated conditions. The tensile bond strength after 25 freeze-thaw cycles (~15°C~25°C) is 1.9 MPa. After 25 freeze-thaw cycles, there is no cracking or peeling. The shrinkage rate is 0.07%, no cracks are generated after solidification, and the thermal conductivity is 0.35 W / (m·K).
[0062] Using the green, low-carbon, energy-saving composite material of this embodiment for the construction and reinforcement of existing masonry houses can effectively improve the structural strength and thermal insulation performance of existing masonry houses. It is suitable for construction projects in high humidity and extreme temperature environments, and exhibits excellent durability and economy.
[0063] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses, characterized in that: The composite material comprises the following components by mass fraction: 20-26 parts of fly ash, 20-25 parts of slag, 10-16 parts of Portland cement, 8-10 parts of high-strength vitrified microspheres, 0.5-1.5 parts of fiber, 0.2-0.5 parts of water reducing agent and 15-30 parts of water.
2. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 1, characterized in that: The composite material comprises the following components by mass fraction: 21-25 parts of fly ash, 21-23 parts of slag, 12-15 parts of Portland cement, 8-10 parts of high-strength vitrified microspheres, 0.8-1.5 parts of fiber, 0.4-0.5 parts of water reducer and 25-28 parts of water.
3. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 2, characterized in that: The composite material comprises the following components by mass fraction: 25 parts of fly ash, 23 parts of slag, 15 parts of Portland cement, 8 parts of high-strength vitrified microspheres, 1.5 parts of fiber, 0.5 parts of water reducing agent and 27 parts of water.
4. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 1, characterized in that: The fiber is polypropylene fiber with a length of 6 mm to 12 mm.
5. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.
6. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 1, characterized in that: The particle size of the high-strength vitrified microspheres is 1 mm to 2 mm, the compressive strength is greater than 2 MPa, and the bulk density is 100 kg / m 3 ~200kg / m 3 , water absorption rate is less than 5%.
7. The green, low-carbon, high-efficiency and energy-saving composite material for reinforcing existing masonry houses according to claim 1, characterized in that: The building material prepared from the composite material has a compressive strength of not less than 10 MPa and a thermal conductivity of less than 0.35 W / m·K during a curing period of 28 days.